2017
DOI: 10.1016/j.tvjl.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of the relationship between Capacity for Care as an animal shelter management model and cat health, adoption and death in three animal shelters

Abstract: Animal shelters struggle to function at their 'right size' in terms of physical, staffing and outcome capacity, especially with seasonal fluctuations in cat intake. To address this, a Capacity for Care (C4C) management model was devised to balance health and welfare requirements of all animals while maintaining or improving goals for positive outcomes, such as adoption or transfer. In this observational study of three shelters, applying the C4C management system gave each organization an optimal average daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…However, decreasing population density in adapted shelters could contribute to decrease stress and, consequently, lower viral loads. A smaller number of animals could contribute to better quality housing, as previously suggested regarding capacity for care (C4C) (KARSTEN et al, 2017). The frequent introduction of new animals might be an explanation for virus reactivation.…”
Section: Sd -Standard Deviationmentioning
confidence: 81%
“…However, decreasing population density in adapted shelters could contribute to decrease stress and, consequently, lower viral loads. A smaller number of animals could contribute to better quality housing, as previously suggested regarding capacity for care (C4C) (KARSTEN et al, 2017). The frequent introduction of new animals might be an explanation for virus reactivation.…”
Section: Sd -Standard Deviationmentioning
confidence: 81%
“…Shelter intake is limited so that capacity is not exceeded. The shelter facilities and polices are consistent with the Capacity for Care (C4C) program to reduce stress, reduce illness, and facilitate the flow of cats and kittens through the shelter [12]. Cats are euthanized only on veterinary advice or if they test seropositive for feline immunodeficiency virus (FIV), testing being routine only for cats considered to be at risk.…”
Section: Methodsmentioning
confidence: 99%
“…Constraints (8) ensure that the number of animals protected in the shelter at the end of the planning horizon cannot exceed the capacity of the shelter. Constraints (9) and (10) are the nonnegativity and binary restrictions of the decision variables. Finally, the objective (1) is to minimize total costs, which are defined by the weighted sum of the number of animals euthanized, the number of animals transferred between shelters, and the number of animals housed in excess of the capacity of the shelter over a planning horizon.…”
Section: Problem Description and Optimization Modelsmentioning
confidence: 99%
“…They showed that animals acquired from shelters had lower rates of euthanasia than most other sources, which indicates that shelter-sourced animals can be considered a preferred source for pet acquisition to help in reducing the number of adoptable pets euthanized. In [9], the authors studied a shelter management model called Capacity for Care (C4C), which calculates the optimal daily population in the shelter based on meeting the shelter's goals of anticipated adoptions and improved animal housing. The results of the study showed that implementing C4C was associated with lower daily populations, increased probability of adoption, and decreased the probability of euthanasia in the shelter.…”
Section: Introductionmentioning
confidence: 99%